Local effect of transdermal isosorbide dinitrate ointment on hand vein diameter - Khanlari, Bettina; Linder, Lilly; Haefeli, Walter E. (European journal of clinical pharmacology, 2001)
To assess the effect of topically applied isosorbide dinitrate (ISDN) ointment on superficial hand veins preconstricted with phenylephrine. Using the hand vein compliance technique, venous diameter changes were measured in a double-blind, randomised, placebo-controlled cross-over trial in 12 healthy volunteers. During preconstriction with phenylephrine, placebo or ISDN ointment was administered to assess the dilator effect of transdermal ISDN. Finally a single i.v. dose of nitroglycerine was administered into the hand vein to assess the maximal venous response to organic nitrovasodilators. ISDN ointment (equivalent to 13.4 +/- 3.61 mg ISDN) caused a significant dilator effect of 39.1 +/- 21.7% (mean +/- SEM, P=0.02) which reached its maximum after 42.5 +/- 16.6 min. Maximum ISDN effects were inversely correlated with venous baseline diameter (r2=0.38, P=0.03) and independent of the amount of ointment applied or the extent of preconstriction (P > 0.3). Similar to nitroglycerine, topical ISDN may relax superficial hand veins within 60 min after application, suggesting that it might ease venepuncture particularly of small vessels. The large variability of the effect and the time to reach the effect, however, restrict its practical usefulness.